A scoping review of the management of acute mastoiditis in children: What is the best approach? - Sarno, Lorenzo Di; Cammisa, Ignazio; Curatola, Antonietta; Pansini, Valeria; Eftimiadi, Gemma; Gatto, Antonio; Chiaretti, Antonio (The Turkish Journal of Pediatrics, 2023)
Background. Acute mastoiditis (AM) is a severe infection of the mastoid air cells that occurs in cases of acute, sub-acute, or chronic middle ear infections. No definitive consensus regarding the management of AM has been identified. The current guidelines include a conservative approach (parenteral antibiotics alone, antibiotics plus minor surgical procedures such as myringotomy with a ventilation tube inserted or drainage of the subperiosteal abscess through retro-auricolar incision or needle aspiration) or surgical treatment (mastoidectomy). The main aim of this review was to evaluate and summarize the current knowledge about the management of pediatric AM by analyzing the current evidence in the literature. Methods. We examined the following bibliographic electronic databases: Pubmed and the Cochrane Library, from the inception date until February 2023. The search was guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISM). The key words used for the search across electronic databases were: `mastoiditis` and `management`; `mastoiditis` and `surgery`; `mastoiditis` and `conservative`; `mastoiditis` and `antibiotics`; `mastoiditis` and `myringotomy`; `mastoiditis` and `grommet`; `mastoiditis` and `drainage`; and `mastoiditis` and `mastoidectomy`. Results. We selected 12 articles involving 1124 episodes of mastoiditis. Some of these studies considered medical therapy alone as a valid first step, whereas others considered a minor surgical intervention as an initial approach along with antibiotic therapy. Considering the studies that evaluated medical therapy as the initial sole treatment option, the success rate of antibiotics alone was 24.6%. Overall, the success rate of minor surgical procedures, excluding mastoidectomy, was 87.7%, whereas the mastoidectomy success rate was 97%. Conclusions. Overall, there is no shared consensus on the diagnostic or therapeutic approach to mastoiditis. Conservative therapy has gained considerable ground in recent times, quite limiting the predominant role of mastoidectomy. Further studies will be necessary to definitely develop standardized protocols shared in the scientific community.